EU Employment Law and Social Policy and the Need to Develop Unitary Electronic Technology of Work by Central and Eastern Member States - Świątkowski, Andrzej (The Policies of the European Union from a Central European Perspective, 2022)
This chapter presents the current situation on the common market caused by the use of electronic employment technologies by entrepreneurs on digital platforms. Its aim is to inspire the Member States of Central and Eastern Europe to take steps to standardize the status of self-employed people on digital platforms. Occasional attempts by the EU institutions to develop a definition of the status of people employed on digital platforms may be treated as a continuation of the practice of multiplying precedents in the jurisprudence of the CJEU. They do not guarantee stable working standards for self-employed people on digital platforms. Keywords: algorithm, algorithmic management, atypical employments, digital platforms, electronic technologies, employee, self-employed, work, working conditions.